2010
DOI: 10.1590/s1807-55092010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos indicadores de rendimento em voleibol em função do resultado do set

Abstract: O presente estudo pretendeu identificar possíveis indicadores de rendimento, adstritos às ações de jogo, diferenciadores do resultado obtido no set em Voleibol. A amostra consistiu em 65.949 ações realizadas em 550 sets da Liga Mundial 2005, "adulto" masculinos. A coleta de dados teve como suporte instrumental o software "Volleyball Information System". Para testar as diferenças nos indicadores de rendimento, entre as equipes que vencem e perdem os sets, se utilizou o teste t de student de medidas independente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
29

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 7 publications
3
17
1
29
Order By: Relevance
“…According to Marcelino and Mesquita (2006), the average attack attempt (corresponding to the term "attack hit" in this study) per match is 97.09±20.25 and the average serve attempt (corresponding to "serve hits") is 88.15±16.17. Marcelino et al (2010) found significant differences in reception, block, defense and between set Winners and Losers, whereas in our study significant differences were found for Set outcome for three in-game roles: Libero for reception and Opposite and Middle blocker for block. In the study by Marcelino and Mesquita (2006), the term "average block attempts" (48.30±14.93) corresponds to contacts in block, "dig attempts" (M=55.63±16.48 attempts) corresponds to contacts in defense and "reception attempts" (70.82±14.59) corresponds to contacts in reception.…”
Section: Hits and Contactscontrasting
confidence: 89%
See 3 more Smart Citations
“…According to Marcelino and Mesquita (2006), the average attack attempt (corresponding to the term "attack hit" in this study) per match is 97.09±20.25 and the average serve attempt (corresponding to "serve hits") is 88.15±16.17. Marcelino et al (2010) found significant differences in reception, block, defense and between set Winners and Losers, whereas in our study significant differences were found for Set outcome for three in-game roles: Libero for reception and Opposite and Middle blocker for block. In the study by Marcelino and Mesquita (2006), the term "average block attempts" (48.30±14.93) corresponds to contacts in block, "dig attempts" (M=55.63±16.48 attempts) corresponds to contacts in defense and "reception attempts" (70.82±14.59) corresponds to contacts in reception.…”
Section: Hits and Contactscontrasting
confidence: 89%
“…For hits, the significant difference for setter and middle blocker by set outcome and in-game role agree with the findings of Marcelino and Mesquita (2010), who found significant differences in attack and serve by set outcome. According to Marcelino and Mesquita (2006), the average attack attempt (corresponding to the term "attack hit" in this study) per match is 97.09±20.25 and the average serve attempt (corresponding to "serve hits") is 88.15±16.17.…”
Section: Hits and Contactssupporting
confidence: 87%
See 2 more Smart Citations
“…The winning teams showed a balance in the percentage of points obtained by terminal actions in top level (Marcelino, et al, 2010), but the way points are obtained may vary depending on age-category competition. The aim of this research study was to find out the way points are obtained in different age groups and categories of men's volleyball.…”
Section: Op 33mentioning
confidence: 98%